2007
DOI: 10.1111/j.1467-6435.2007.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering and Income – The Fallacy of the Good Samaritan?

Abstract: This paper explores individual motives for volunteering. The analysis is based on the interpretation of volunteering as a consumption good (consumption model) or as a mean to increase individual's own human capital (investment model). We present an econometric framework taking into account self selection into volunteering and simultaneity between the volunteering decision and the determination of income in order to test these two models and to identify the underlying motives.We find strong statistical evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(119 citation statements)
references
References 55 publications
5
108
1
5
Order By: Relevance
“…Consequently, individuals with volunteering experience tend to be hired or command a higher wage (Katz and Rosenberg , 2005) Empirical data for the most part does not contradict this line of reasoning. Hackl, Halla, and Pruckner (2007) using Austrian data found evidence of a wage premium of 18.7 percent on average for volunteers. A Canadian study found a 6-7 percent return of volunteering in annual earnings for Canadian workers (Day and Devlin, 1998).…”
Section: Literature Revi Ew: the Payoff Of Volunteering For Universitmentioning
confidence: 99%
“…Consequently, individuals with volunteering experience tend to be hired or command a higher wage (Katz and Rosenberg , 2005) Empirical data for the most part does not contradict this line of reasoning. Hackl, Halla, and Pruckner (2007) using Austrian data found evidence of a wage premium of 18.7 percent on average for volunteers. A Canadian study found a 6-7 percent return of volunteering in annual earnings for Canadian workers (Day and Devlin, 1998).…”
Section: Literature Revi Ew: the Payoff Of Volunteering For Universitmentioning
confidence: 99%
“…We are aware of seven previous studies by economists that confronted the aforementioned theoretical expectations with the empirical reality: Day and Devlin (1997), Day and Devlin (1998), Prouteau and Wolff (2006), Hackl et al (2007), Sauer (2015, Wilson et al (2017) and Cozzi et al (in press). Table 1 summarises the research results published, between 1997 and 2017, either as a journal article or as a working paper.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, it was found that returns to volunteering accounted for 6-7 per cent of annual earnings (Day & Devlin 1998). In Austria, the number of volunteering hours plays a major role in explaining the wage premium through the accumulation of human capital (Hackl et al 2007). On the assumption that those who engage in unpaid work are more active in finding a job and more likely to get a paid job because they have accumulated local work experience or other forms of human capital, which are more valued by local employers, we propose hypotheses 3a and 3b.…”
Section: Hypothesis 2bmentioning
confidence: 99%